Isoquinoline alkaloids from Thalictrum glandulosissimum and their network analysis of chemotaxonomic value. (April 2022) - Shen, Xiaojing; Yan, Yuanfeng; Li, Xingyu; Ma, Junrong; Xie, Fujuan; Zhou, Shaoqin; Feng, Yu; Yin, Tianpeng
Abstract: A phytochemical investigation of Thalictrum glandulosissimum (Finet et Gagnep.) W. T. Wang & S. H. Wang (Ranunculaceae), a species used medicinally in China, led to the isolation and identification of nine isoquinoline alkaloids, including four protoberberines (compounds 1 –4 ), a protopine-type alkaloid (5 ), a bridge-protoberberine-type alkaloid (6 ), and three bis-benzylisoquinolines (7 –9 ). Among them, thalictricavine (4 ) and valachine (6 ) are reported for the first time in the genus Thalictrum. Furthermore, three alkaloids (7 –9 ) have not previously been isolated from this species. In addition, network analysis was carried out to explore their possible chemotaxonomic values among species in the Thalictrum genus. The results showed that some of these compounds such as thalictricavine (4 ) and valachine (6 ) showed limited distribution in the genus, which could help to narrow species identification to T. glandulosissimum where other phenotypic characters are limited. Highlights: Nine isoquinoline alkaloids were isolated from Thalictrum glandulosissimum. Two compounds were isolated in the genus Thalictrum for the first time, and three compounds were isolated from the species Thalictrum glandulosissimum for the first time. The compound-species network study demonstrated the chemotaxonomic value of the isolated compounds.